Participatory Evaluation of Effectiveness of Farmer-Led Adaptation Strategies to Climate Change in Eastern Uttar Pradesh - Yadav, Preeti; Maiti, Sanjit; Jha, S. K.; Meena, H. R.; Bhakat, Mukesh; Dixit, A. K. (Indian Journal of Extension Education, 2021)
India has shown high vulnerability towards the impact of climate change due to the dependency of 58 per cent of Indiaâ€™s population on agriculture. The study was carried on 180 respondents in three districts selected randomly of eastern Uttar Pradesh to evaluate farmer-led adaptation strategies to the impact of climate change, activities that are predominantly led by farmers to make them more adaptable to long-term changes in weather patterns. Â All the respondents had experienced extreme climatic events in the last 5-10 years, making the region climate-prone. Nine farmersâ€™-led adaptation strategies to climate change followed in crop farming were documented and quantified by using Climate Change Adaptation Index. Adaptation strategies were evaluated using the Quantification of Indigenous Knowledge method (QuIK) method; by involving the key informants followed by peer farmers. Crop diversification, use of high yielding varieties of crops and preparations of bunds to control water flow were the most preferred adaptation strategies to climate change. The irregular rainfall increased the incidence of floods in eastern Uttar Pradesh; thus, the preparation of bunds to regulate water flow in crop fields was the most efficient adaptation strategy.